Cultures in conversation - Carbaugh, Donal A. (Mahwah, N.J. : Lawrence Erlbaum, 2005)
"Cultures in Conversation introduces readers to the ethnographic study of intercultural and social interactions through the analysis of conversations in which different cultural orientations are operating. Author Donal Carbaugh presents his original research on conversation practices in England, Finland, Russia, Blackfeet County, and the United States, demonstrating how each is distinctive in its communication codes, particularly in its use of symbolic meanings, forms of interaction, norms, and motivational themes. Examining conversation in this way demonstrates how cultural lives are active in conversations and shows how conversation is a principle medium for the coding of selves, social relationships, and societies." "Representing 20 years of research, this text offers unique insights into the ways social interactions not only gain shape from, but are formative of cultures. It makes a significant contribution to communication scholarship, and will be illuminating reading in courses which focus on cultural communication, language and social interaction, intercultural pragmatics, and linguistics."--BOOK JACKET.
Includes bibliographical references (p. 133-143) and index.
committed to retain
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Conversation analysis; Intercultural communication; Electronic books